Gramática e gramaticalização: os possessivos em português - Dantas, Ana Maria Ribeiro (2008)
This study is situated on the grammar of the Portuguese language with discursive-functional approach and is focused on the diversity of uses grammar morphemes, called our traditional grammarian "possessive pronouns adjectives." The study is justified because it had been found in the teaching of Portuguese language and Portuguese foreign language, a lack of studies that focus on description of rules underlying the semantic values in the different dimensions textual and discursive. Such studies are needed to solve problems presented by foreigners, and also Brazilian, in understanding the operation of "possessive pronouns adjectives" as arising from enunciate intentions. It is, moreover, because they have verified that there is no treatment discursive-functional language for "possessive" by traditional grammars, that situate the morphemes in the dimension of the sentence, from systemic rules in order not to consider the language in effective use. Thus, the general aim of this study is contributing to the studies that inter-related grammar and grammaticalization for the treatment of enunciativos phenomena of language. They are specific objectives: 1. to seek, in the history of the portuguese language, evidence of systemic grammar and grammaticalization of morphemes "possessive" from the semantic value of ownership and its modifications, 2. to examine in effective use of brazilian portuguese, relations between subject and progression semantics of text to the use of morphemes possessive in the text-product, 3. to deal the lexical choices and its relations with grammar morfossintaxe. The theoretical aspects are considered in the search for the Pragmática, the Critical Analysis of Discourse, the Traditional Grammar, the Functional Grammar to deal the dimensions textual communicative, textual discourse and processes of grammaticalization. The results indicate that: 1.em relation to morpheme possessive, synchronic at the same time, use forms together in the past with the present forms, 2. there are systemic grammatical rules that are applied in the construction textual-discursive, namely: Rule 1 - the nominalisation of the predicate and use of the possessive morpheme by subject; Rule 2 - the correlation of morpheme possessive noun by inflections of gender and number; Rule 3 to Serve as the morpheme possessive adjective, before the noun; Rule 4 - the morpheme possessive with function of the pronoun in order to replace the lexical sintagms. These rules allow understand the cause of tradicional brazilian grammar, post NGB, classify the possessive pronouns in adjectives